Analysis of Correlation between Workload and Work Attitudes Toward Work Fatigue (Case Study in Kaliotik Lamongan Restaurant Workers) - Rohmia Fina Ansori (Universitas Airlangga, 2020)
Introduction: Currently, Culinary becomes a promising business, so does Lamongan Kaliotik Resto, one of the famous restaurant in Lamongan. The high number of customer visits risks the workforce from work fatigue. The demand for production in order to fulfill the consumer needs leads to an excessive workload which is handed to the workers in the Kaliotik Lamongan restaurant. Moreover, high mobility in the food production process potentially creates non-ergonomic work attitudes. Therefore, all of those factors can lead the workers experiencing work fatigue. The purpose of this study was to analyze the relationship between workload and work attitude with work fatigue at Kaliotik Lamongan Resto workers. Methods: This study was observational descriptive which was done by using cross-sectional. The population in this study was all workers at the Kaliotik Lamongan Resto, which consisted of 13 people who worked in the kitchen and cashier kitchen section. The sampling technique used was the total population technique. Data collection includes physical workload measurements, assessment of work attitude with The Rapid Upper Limb Assessment (RULA) method and work fatigue measurements using a reaction timer. The study was analyzed using the Spearman correlation test. Results: Showed that the workload with work fatigue had a relationship with the strength of the moderate relationship (r = 0.415) and work attitudes with work fatigue showed a low strong relationship (r = 0.389). Conclusion: Excessive workload is the main factor which causes work fatigue in workers, in contrary, work attitude is not a factor of work fatigue.Keywords: physical workload, work attitude, work fatigue